Seroepidemiology of Human Hydatidosis Using AgB-ELISA Test in Isfahan City and Suburb Areas, Isfahan Province, Central Iran - Parisa ILBEIGI; Mehdi MOHEBALI; Eshrat Beigom KIA; Mohammad SABERINASAB; Mojgan ARYAEIPOUR; Negar BIZHANI; Mohammad Bagher ROKNI (Tehran University of Medical Sciences, 2015)
Background: The aim of this study was to conduct a sero-epidemiological survey in Isfahan City and suburb areas, central Iran to detect the rate of human hydatidosis using ELISA test. Methods: Overall, 635 serum samples were collected from subjects referred to different health centers in urban and rural regions of the city. Sera were analyzed using Ag-B ELISA test. Ten μg/ml antigens, serum dilutions of 1:500 and conjugate anti-human coombs with 1:10000 dilutions were utilized to perform the test. All subjects filled out a questionnaire and an informed consent. Data analysis was conducted using SPSS 18 software. Cut-off was calculated as X+3 SD. Results: Cut-off value was calculated 0.19. Seven cases (1.1%) were seropositive for hydatidosis by ELISA test. The sero-prevalence of hydatidosis was 0.27% among females and 2.24% among males (P=0.019). Age group of 60-69 years old, with 2.59% as prevalence had the highest rate of positivity. There was no significant difference as regards age groups, job, residency, contact by dog and literacy. According to job, self-employed people had the highest rate of infection as 3.05%. The sero-prevalence of infection was 1.14% in diploma and 1.13% in illiterates. As regards residency, urban life (1.49%) showed no significant difference with rural life. Conclusion: The rate of prevalence in this region showed that necessary cautions should be taken into account to monitor the spread of human hydatidosis in this region. In comparison with other studies, the rate of infection was roughly less than other regions.